Phytochemical Analysis and Potential Pharmacological Activity of Frangipani Flower Simplicia (Plumeria spp.) as a Source of Medicinal Ingredients - Evi Riszka Nurhapit; Nurfadhilla, Fitri; Ilham Bintang Pratama; Marsella Mideliani Jured; Sigit Roma Rezki Harahap; Wipena Fariza (HM Publisher, 2024)
Frangipani flower simplicia contains various phytochemical compounds, such as alkaloids, flavonoids, saponins, and tannins. These phytochemical compounds have the potential to have various pharmacological activities, such as antibacterial, antifungal, anti-inflammatory, antioxidant, and anticancer. This study aims to explore the phytochemical analysis and potential pharmacological activity of frangipani flower simplicia (Plumeria spp.) as a source of medicinal ingredients. The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) regarding phytochemical analysis and potential pharmacological activity of frangipani flower simplicia (Plumeria spp.). The frangipani flower is a traditional medicinal plant that has various benefits. The phytochemical content contained in frangipani flowers, such as alkaloids, flavonoids, saponins, and tannins, has the potential to have various pharmacological activities, such as antibacterial, antifungal, anti-inflammatory, antioxidant, and anticancer.